2021
DOI: 10.7759/cureus.16887
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Grade 3 Gliomas: Correlation of MRI Findings With Prognosis

Abstract: Background and objectivePostoperative radiotherapy is usually indicated for both grade 3 glioma and grade 4 glioblastoma. However, the treatment results and tumor features of grade 3 glioma clearly differ from those of glioblastoma. There is limited information on outcomes and tumor progression for grade 3 glioma. In this study, we evaluate the result of postoperative radiotherapy for grade 3 glioma and focus on the correlation of MRI findings with prognosis. MethodsIn this study, 99 of 110 patients with grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The results of this study based on quantitative evaluation of edema are consistent with this finding. Liang et al found that the E/T ratio contributes significantly to OS [ 7 ], and other reports have shown that PE (without consideration of tumor volume) is a prognostic factor in G3 or G4 glioma [ 3 , 6 ]. Therefore, the E/T ratio and PE are both useful prognostic factors for gliomas that can be objectively assessed on conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study based on quantitative evaluation of edema are consistent with this finding. Liang et al found that the E/T ratio contributes significantly to OS [ 7 ], and other reports have shown that PE (without consideration of tumor volume) is a prognostic factor in G3 or G4 glioma [ 3 , 6 ]. Therefore, the E/T ratio and PE are both useful prognostic factors for gliomas that can be objectively assessed on conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Such edema promotes tumor cell infiltration into the surrounding area, which extends the range over which the tumor can expand [2]. In Grade 3 (G3) and Grade 4 (G4) gliomas, extensive preoperative edema (PE) can be readily identified on magnetic resonance imaging (MRI) and has been found to be a poor prognostic factor [3][4][5][6]. The degree of edema can be classified into categories, but may also be described numerically [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation